2008
DOI: 10.1001/archneurol.2007.8
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Purkinje Cell Number in Essential Tremor

Abstract: Background: Clinical and functional imaging evidence suggests that cerebellar dysfunction occurs in essential tremor (ET). In recent postmortem studies, we documented increased numbers of torpedoes (Purkinje cell axonal swellings) in ET patients without Lewy bodies. Purkinje cell loss, however, has never been rigorously assessed. Objective: To quantitatively assess the number of Purkinje cells in brains of ET patients and similarly aged controls. Methods: Postmortem cerebellar tissue was available in 14 ET cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
194
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 198 publications
(206 citation statements)
references
References 41 publications
8
194
0
4
Order By: Relevance
“…Although our methodologic approach speaks to the robustness of our findings, neuropathologic confirmation of our preliminary data is warranted. A recent neuropathologic study found mild and inhomogeneous cerebellar pathologic changes in patients with sporadic ET, 26 but the underlying neurodegenerative processes in head and arm ET have not yet been reported.…”
Section: Discussionmentioning
confidence: 96%
“…Although our methodologic approach speaks to the robustness of our findings, neuropathologic confirmation of our preliminary data is warranted. A recent neuropathologic study found mild and inhomogeneous cerebellar pathologic changes in patients with sporadic ET, 26 but the underlying neurodegenerative processes in head and arm ET have not yet been reported.…”
Section: Discussionmentioning
confidence: 96%
“…Much of the literature supports that ET is a disorder of cerebellar dysregulation, including the presence of intention tremor [Leegwater- Kim et al 2006;Louis et al 2009b], gait ataxia [Singer et al 1994;Stolze et al 2001], oculomotor abnormalities [Helmchen et al 2003] and problems with dysrhythmia and motor learning [Trillenberg et al 2006;Avanzino et al 2009;Bares et al 2010;Farkas et al 2006;Shill et al 2009;Kronenbuerger et al 2007]. In addition, postmortem studies in ET have indicated the presence of a variety of structural and degenerative changes in the cerebellum, including increased number of Purkinje cell axonal swellings ('torpedoes') [Louis et al 2007b;Axelrad et al 2008], increased number of displaced or heterotopic Purkinje cells [Kuo et al 2011], reduction in number of Purkinje cells in some studies [Axelrad et al 2008] [Bucher et al 1997], positron emission tomography [Jenkins et al 1993;Wills et al 1994;Colebatch et al 1990], 1 H magnetic resonance spectroscopic imaging [Louis et al 2002;Pagan et al 2003], diffusion tensor imaging [Shin et al 2008;Klein et al 2011;Nicoletti et al 2010], voxelbased morphometry [Benito-Leon et al 2009;Quattrone et al 2008] and studies using other automated volumetric methods [Cerasa et al 2009] which demonstrate the presence of functional, metabolic and structural abnormalities in the cerebellum of ET patients.…”
Section: Current Literature On the Relationships Between Et And Cognimentioning
confidence: 99%
“…2. Linear density of Purkinje cells was determined by counting Purkinje cells nuclei per millimeter line length throughout the section [19]. 3.…”
Section: Morphometrical Studymentioning
confidence: 99%